Quality Assessment for PCR-based Minimal Residual Disease in Lymphoma: 10 Years of Cross-laboratory Standardization Process Within the Fondazione Italiana Linfomi MRD Network. Issue 10 (6th October 2021) - Mantoan, Barbara; Genuardi, Elisa; Ferrante, Martina; Della Starza, Irene; Ciabatti, Elena; Grassi, Susanna; De Novi, Lucia Anna; Cavalli, Marzia; Mannu, Claudia; Gazzola, Anna; Bomben, Riccardo; Degan, Massimo; et al.
Abstract : Supplemental Digital Content is available in the text.